Novel adenovirus detected in captive bottlenose dolphins (Tursiops truncatus) suffering from self-limiting gastroenteritis - Rubio Guerri, Consuelo; García Párraga, Daniel; Nieto Pelegrín, Elvira; Melero Asensio, Mar; Álvaro, Teresa; Valls, Mónica; Crespo, Jose Luis; Sánchez-Vizcaíno Rodríguez, José Manuel (BMC Veterinary Research, 2015)
BACKGROUND Adenoviruses are common pathogens in vertebrates, including humans. In marine mammals, adenovirus has been associated with fatal hepatitis in sea lions. However, only in rare cases have adenoviruses been detected in cetaceans, where no clear correlation was found between presence of the virus and disease status. CASE PRESENTATION A novel adenovirus was identified in four captive bottlenose dolphins with self-limiting gastroenteritis. Viral detection and identification were achieved by: PCR-amplification from fecal samples; sequencing of partial adenovirus polymerase (pol) and hexon genes; producing the virus in HeLa cells, with PCR and immunofluorescence detection, and with sequencing of the amplified pol and hexon gene fragments. A causative role of this adenovirus for gastroenteritis was suggested by: 1) we failed to identify other potential etiological agents; 2) the exclusive detection of this novel adenovirus and of seropositivity for canine adenoviruses 1 and 2 in the four sick dolphins, but not in 10 healthy individuals of the same captive population; and 3) the virus disappeared from feces after clinical signs receded. The partial sequences of the amplified fragments of the pol and hexon genes were closest to those of adenoviruses identified in sea lions with fatal adenoviral hepatitis, and to a Genbank-deposited sequence obtained from a harbour porpoise. CONCLUSION These data suggest that adenovirus can cause self-limiting gastroenteritis in dolphins. This adenoviral infection can be detected by serology and by PCR detection in fecal material. Lack of signs of hepatitis in sick dolphins may reflect restricted tissue tropism or virulence of this adenovirus compared to those of the adenovirus identified in sea lions. Gene sequence-based phylogenetic analysis supports a common origin of adenoviruses that affect sea mammals. Our findings suggest the need for vigilance against adenoviruses in captive and wild dolphin populations. Centro de Vigilancia Sanitaria Veterinaria (VISAVET) TRUE pub